Social rejection during school years and the development of negative attitudes toward minority groups in adulthood. (June 2018) - Gross, Zehavit; Maor, Rotem
Highlights: The current research indicate that a violent act related to early social rejection is rejection of minority groups. Rejection contributes to low self-esteem in adulthood, which in turn contributes to negative attitudes toward outgroups. Rejection contributes to minimal relations with outgroups, which in turn contributes to negative attitudes toward them.